A novel 8-hydroxyquinoline-pyrazole based highly sensitive and selective Al(iii) sensor in a purely aqueous medium with intracellular application: experimental and computational studies. (31st March 2016) - Islam, Abu Saleh Musha; Bhowmick, Rahul; Mohammad, Hasan; Katarkar, Atul; Chaudhuri, Keya; Ali, Mahammad
Abstract : A new 8-hydroxyquinoline-pyrazole based probe senses Al 3+ and hence Al 3+ –8Q-NH-Pyz complex mediated F − in a purely aqueous medium. Abstract : A new 8-hydroxyquinoline-pyrazole based highly sensitive and selective Al 3+ sensor, 8Q-NH-Pyz (H2 L 3 ), was found to exhibit a turn-on fluorescence enhancement (FE) as high as 157 fold with K d = (1.76 ± 0.06) × 10 −5 M. The 1 : 1 binding stoichiometry was revealed from the linear fit of ( F max − F 0 )/( F − F 0 ) vs. 1/[Al 3+ ] of the fluorescence titration data which was further substantiated by Job's method and HRMS studies. The LOD determined by 3 σ methods was found to be 4.29 nM and quantum yields were determined to be 0.002 and 0.28 for the ligand and its Al 3+ complex, respectively. The tentative coordination environment in the[Al(L 3 )(H2 O)] + complex was delineated by DFT calculations. TDDFT calculations reveal spectral features comparable to the experimental ones. This constitutes the first report on the fluorescence sensing of Al 3+ and hence F − in a purely aqueous medium.